SKRINING PENYAKIT TIDAK MENULAR PADA MASYARAKAT KECAMATAN NAMBO KOTA KENDARI - Agusalim Ali; I Putu Sudayasa; Jamaluddin Jamaluddin; Arimaswati Arimaswati; Andi Nurcholida; La Rangki La Rangki (STIKES NGUDIA HUSADA MADURA, 2021)
Non-communicable diseases (NCDs) are responsible for at least 70% of deaths in the world. Although it cannot be transmitted from person to person or from animal to person, weak control of risk factors can lead to an increase in cases every year. Nationally, the results of Riskesdas 2018 show that the prevalence of the population with high blood pressure is 34.11%. The prevalence of high blood pressure in women (36.85%) is higher than that of men (31.34%). The prevalence in urban areas is slightly higher (34.43%) compared to rural areas (33.72%). Prevalence increases with age. This screening activity aims to determine blood pressure, blood glucose levels, uric acid and cholesterol in the people of Nambo sub-district. The measurement results showed that most of the people who participated in this screening activity experienced hypertension and only a small portion had high levels of glucose, uric acid and cholesterol.